1996
DOI: 10.1002/j.1556-6676.1996.tb02303.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Declared and Undeclared College Students on Career Uncertainty and Involvement in Career Development Activities

Abstract: As reported in current research, many if not most freshmen and sophomores in colleges and universities who are declared as well as undeclared about their academic majors express uncertainty about their careers and lack the level of involvement in the career development process (especially self-assessment, career exploration, and career decision making) necessary to make educated career decisions. This research study, using both quantitative and qualitative research processes, identifies and examines difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 15 publications
5
48
0
1
Order By: Relevance
“…Preliminary results are in line with earlier arguments (e.g., Berntson et al, 2006;Blustein, 1997;Zikic & Klehe, 2006;Orndorff & Herr, 1996) about the mitigating effect of such variables as employability and career exploration, and the exacerbating effect of career uncertainty. On the other hand, the second hypothesis cannot be fully confirmed as only a few significant interactions were obtained and the moderator analysis has posed many questions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Preliminary results are in line with earlier arguments (e.g., Berntson et al, 2006;Blustein, 1997;Zikic & Klehe, 2006;Orndorff & Herr, 1996) about the mitigating effect of such variables as employability and career exploration, and the exacerbating effect of career uncertainty. On the other hand, the second hypothesis cannot be fully confirmed as only a few significant interactions were obtained and the moderator analysis has posed many questions.…”
Section: Discussionsupporting
confidence: 89%
“…This category includes such factors as perceived career barriers (Swanson, Daniels, & Tokar, 1996), dysfunctional career thoughts (Sampson, Peterson, Lenz, Reardon, & Saunders, 1998) or career uncertainty (Orndorff & Herr, 1996;Ito & Brotheridge, 2001), to name just a few. This study focuses on career uncertainty, as this variable is the most person-centred.…”
Section: Introductionmentioning
confidence: 99%
“…From the sample population of 84 prospective students, 42 subjects (50%) described themselves as predominantly uncertain of a career choice. This outcome supports Beerlall's (1997) finding that the levels of educational and vocational indecision amongst first-entry university students were high, as well as previous research suggesting the need for career counselling amongst university students (Jones, Gorman & Schroeder, 1989;Orndorff & Herr, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Orndorff and Herr (1996) confirmed that research indicates a comprehensive and intense need for career planning and guidance amongst high school and university students, with the choice of a career and a major being priorities.…”
mentioning
confidence: 70%
“…Other students wrestle with which faculty to select, never mind what career to pursue. Research has found that after declaring a major, students experience less academic and career indecision than their undeclared peers (Orndorff and Herr 1996). However, actually declaring a major may not be the only way to reduce uncertainty: Santos and Coimbra (2000) suggest that career indecision is related to limited career exploration and by extension, to students' intentions.…”
Section: The Role Of the Learning Environmentmentioning
confidence: 97%